Emerging trends in contact lens-related infections. Issue 4 (July 2016) - Cheung, Natalie; Nagra, Parveen; Hammersmith, Kristin
Abstract : Purpose of review: This article reviews the literature on past and recent trends in contact lens-related microbial keratitis from bacterial, fungal, and Acanthamoeba infections. Recent findings: Contact lens wear is the most important risk factor for microbial keratitis. Despite increased use of daily disposable contact lens wear, the incidence of bacterial ulcers related to contact lens wear remains high. Overnight contact lens wear is the leading risk factor in contact lens-related bacterial infections. There may be a trend towards increasing antibiotic resistance of Gram-positive bacteria to fourth-generation fluoroquinolones. The incidence of Acanthamoeba and fungal infections, despite resolution of two outbreaks involving multipurpose solutions, are also on the rise. Summary: Contact lens-related microbial keratitis is rising and may be associated with more severe, vision threatening, infections.